2001
DOI: 10.1128/aem.67.2.769-773.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Selenite by Ralstonia metallidurans CH34

Abstract: Ralstonia metallidurans CH34 (formerly Alcaligenes eutrophus CH34) is a soil bacterium characteristic of metal-contaminated biotopes, as it is able to grow in the presence of a variety of heavy metals. R. metallidurans CH34 is reported now to resist up to 6 mM selenite and to reduce selenite to elemental red selenium as shown by extended X-ray absorption fine-structure analysis. Growth kinetics analysis suggests an adaptation of the cells to the selenite stress during the lag-phase period. Depending on the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 24 publications
7
78
1
2
Order By: Relevance
“…Consistent with the involvement of glutathione in the dissimilatory reduction of selenite, various proteobacteria belonging to these groups have been shown to tolerate millimolar levels of selenite (6,12,19,20). In contrast, a broad survey of selenite tolerance in bacteria (63 species) demonstrated that most species (81%) are not able to grow in the presence of 0.2 mM selenite (25).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Consistent with the involvement of glutathione in the dissimilatory reduction of selenite, various proteobacteria belonging to these groups have been shown to tolerate millimolar levels of selenite (6,12,19,20). In contrast, a broad survey of selenite tolerance in bacteria (63 species) demonstrated that most species (81%) are not able to grow in the presence of 0.2 mM selenite (25).…”
Section: Discussionmentioning
confidence: 91%
“…6,12,19,20). The threshold of selenite concentration that the cells are able to reduce may reflect, at least in part, the large requirement of oxidative stress enzymes for this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain is a good candidate for the accelerated bioremediation of systems contaminated by high levels of cadmium Sharma et al 2000 Subsurface sediment Uranium Stimulation of dissimilatory metal reduction activity of an enrichment of microorganisms closely related to Pseudomonas and Desulfosporisinus sp. which promote the reductive precipitation of uranium Nevin et al 2003 Selenite polluted site Selenium Ralstonia metallidurans CH34 can reduce selenite to elemental red selenium, that is highly insoluble Roux et al 2001 Subsurface sediment Subsurface environments Uranium Biofilm of the sulfate reducing bacterium Desulfovibrio desulfuricans attached to hematite (a-Fe 2 O 3 ) surface can accumulates both U(VI) and U(IV) and thus can limit the transport of uranium in subsurface environments Neal et al 2004 substances. Research in bioremediation is now opening the virtually infinite possibilities inherent in enzymatic systems.…”
Section: Cadmiummentioning
confidence: 99%
“…Firstly, this unusual multiple toxic metal ion-resistant bacterium has been a model for how microbes handle such toxic metal (loids) from the time of its first isolation (Mergeay et al 1978(Mergeay et al , 1985. Moreover, it continues to be a useful model, as seen in this series of reports as well as in any search of the literature, used for an expanding range of interests from metal response physiology (Nies et al 1990(Nies et al , 1989Nies 2000;Roux et al 2001;Sendra et al 2006) and basic molecular genetics (Lejeune et al 1983), to genomics (the organism is unusual in having two chromosomes plus two large plasmids; Mergeay et al 2003), microbial ecology (Vander Auwera, this series), to applications in environmental biotechnology (Diels, this series) and even in space research (Leys, this series).…”
mentioning
confidence: 99%